Relationship Between Birth Weight Against Weight Gain 12 Months of Age in Babies at Lubuklinggau City - Muhammad Ridho Nugroho; Ratu Ayu Dewi Sartika (STIKes Hang Tuah Pekanbaru, 2019)
The baby's weight gain is very rapid, but the rate of weight gain is getting less and less. At the age of 5 months, a baby weighs twice his birth weight, while at 1 year his weight reaches three times his birth weight, and at 2 years his weight weighs four times his birth weight. The purpose of this study was to determine the relationship between birth weight and factors influencing weight gain at the age of 12 months in babies born at the midwife independent practice clinic (BPM) in Lubuklinggu City, South Sumatra Province in 2019. Sample of 108, research design cross sectional. The results showed there was a relationship between birth weight (p value = 0.001) and immunization status (p value = 0.017) to the baby's weight gain at 12 months of age.